Exploring the Dimensions of Multicultural Education and its Implication in Teaching Learning - Sherpa, Dawa (Interdisciplinary Research in Education, 2019)
This article aims to present the concept and needs of multicultural education in Nepal. This paper is based on extensive review of literature on multicultural education in Nepal. Multicultural education provides equal educational opportunities for all races, nations and groups of different cultures. Cultural values, ethics, norms and practices are focused on multicultural education. It helps to find out the cultural knowledge and skills in the learners and communicate with other ethnic groups. Multicultural curriculum can prepare individuals and groups with diverse backgrounds to live peacefully in a society. Multicultural education promotes the strength and value of cultural diversity. Moreover, it also ensures human rights and respect to one another and the acceptance of alternative life styles of people, and the promotion of social justice.